Identification of Student Learning Styles based on Multiple Intelligences Aspects using the Dempster-Shafer Method - Hidayat, Julkarnain; Putri, Raissa Amanda (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Learning style refers to an individual's process of understanding and absorbing information, which is influenced by sensory preferences, problem-solving strategies, and communication styles. This research explains the learning styles of high school students by utilizing the theory of multiple intelligences, identifying seven aspects: visual, auditory, kinesthetic, verbal-linguistic, logical-mathematical, social-interpersonal, and solitary-intrapersonal. With a better understanding of students' learning styles, teachers can devise more effective teaching methods, improving learning outcomes. This research aims to apply the Dempster-Shafer method in an expert system to identify the learning styles of high school students, especially in SMA Swasta Dharmawangsa Medan. Through interviews with guidance teachers and questionnaires from grade X students, the expert system will provide information and customized learning methods, improving teacher understanding and student participation. With PHP-based web technology, the system is designed to simplify the process and provide a user-friendly interface and efficient data management, in the hope of creating a more productive and supportive learning environment.